2021
DOI: 10.4018/ijssmet.290332
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Affecting the Attraction and Retention of Academic Employees at the Durban University of Technology

Abstract: The objective of the study was to explore the factors affecting the attraction of academic employees and assessed the factors influencing their retention at the Durban University of Technology. This was a qualitative study conducted among 12 academics who were purposefully selected. The study found that the university was not doing enough to attract academic talent as job offers appeared to be the dominant reason for employees entering the employ of the institution. The study also found training and mentorship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A study conducted on recent increases in employee turnover in the UAE's banks demonstrated that UAE nationals left their jobs because they were dissatisfied with career advancements, financial and retirement benefits, and relationships with co-workers and supervisors (Alqubati et al, 2019). Hoque and Tshutsha (2022) asserted that organizations are compelled to design employee assistance programs in order to improve working environments, as such programs affect employee satisfaction and overall retention. Some of these programs are "flexible work hours and special leave, such as maternity leave, adoption leave, extended leave and personal leave" (Hoque & Tshutsha, 2022, p. 4).…”
Section: Inclusion In the Uae Contextmentioning
confidence: 99%
“…A study conducted on recent increases in employee turnover in the UAE's banks demonstrated that UAE nationals left their jobs because they were dissatisfied with career advancements, financial and retirement benefits, and relationships with co-workers and supervisors (Alqubati et al, 2019). Hoque and Tshutsha (2022) asserted that organizations are compelled to design employee assistance programs in order to improve working environments, as such programs affect employee satisfaction and overall retention. Some of these programs are "flexible work hours and special leave, such as maternity leave, adoption leave, extended leave and personal leave" (Hoque & Tshutsha, 2022, p. 4).…”
Section: Inclusion In the Uae Contextmentioning
confidence: 99%
“…Despite these well-attempted efforts, HEIs still face a severe problem of retention, management, and attraction of academics who can assist in achieving the national economic objectives of any country (Hoque & Tshutsha, 2022). Highly qualified academics are increasingly moving to the private sector and other HEIs, which can offer better rewards and benefits (Erasmus et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Successful academic institutions depend on having the right number of skilled and capable academic staff who should be well motivated in order to contribute to the institution. However, in order to motivate these staff, factors including satisfactory salary, job design, internal communication, as well as better and real-time decision-making need to be put into consideration (Galli, 2020;Hoque & Tshutsha, 2022). It is imperative that academic institutions attract, motivate, and retain knowledgeable academic staff in order to remain abreast with OBF requirements (Arman, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its historical nature and the increasing globalization, the country has been suffering insufficient human resources, especially in the academic domain. In the South African perspective, the demand for highly skilled academic employees in institutions of higher education and training has remained high, and this trend is likely to continue (Hoque & Tshutsha, 2022). As a result many universities fail to attract and/or retain highly qualified academic staff, which causes them to fall short of attaining the required scores for OBF (Segooa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%